Sweet's Syndrome: A Classical Presentation of a Rare Disease - Arash Mollaeian MD; Hadi Roudsari MD; Ebrahim Talebi MD (SAGE Publishing, 2019)
Sweet's syndrome, also known as acute febrile neutrophilic dermatosis, is a rare disorder that typically presents with rapid appearance of tender skin lesions accompanied by fever and leukocytosis with neutrophilia. Its pathogenesis is not fully understood. The syndrome is generally classified into classical, malignancy-associated, and drug-induced categories, each of which has its specific characteristics. In this article, we present a case of classical Sweet's syndrome in a woman who presented with an acute viral illness.